2018
DOI: 10.1080/13102818.2018.1443400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical components and antioxidant capacity of different kiwifruit (Actinidiaspp.) genotypes grown in China

Abstract: Kiwifruit from eight Actinidia genotypes were evaluated for soluble sugar content (SSC), titratable acidity content (TAC), sugar-acid ratio (SAR), vitamin C (Vc) content, superoxide dismutase (SOD) activity, total phenolic content (TPC), total flavonoid content (TFC) and antioxidant capacity using four assays: 2,2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical-scavenging assay; 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging assay; oxygen radical absorbance capacity (ORAC) and ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
(43 reference statements)
4
25
0
Order By: Relevance
“…Furthermore, these results indicated that the polyphenols are the main compounds for antioxidant capacities in O. aristatus. The results are in line with previous reports in O. aristatus and other different crops 38,44,45 . Besides, several reports shows association between polyphenol contents and antioxidant properties, but no one highlighted the mechanism of the association between polyphenol compounds and antioxidants in O. aristatus.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, these results indicated that the polyphenols are the main compounds for antioxidant capacities in O. aristatus. The results are in line with previous reports in O. aristatus and other different crops 38,44,45 . Besides, several reports shows association between polyphenol contents and antioxidant properties, but no one highlighted the mechanism of the association between polyphenol compounds and antioxidants in O. aristatus.…”
Section: Discussionsupporting
confidence: 93%
“…In H9c2 rat cardiac myocytes cells induced by hypoxia in cardiomyocytes treated with angiotensin II, treatment with 1.25 and 2.5 mg/ml polysaccharide of A. chinensis alleviated cardiac hypertrophy, decreased mitochondrial dysfunction and reduced cardiomyocytes apoptosis by decreasing the apoptosis-associated genes expression like mitochondria associated-1 and caspases3/8/9 , and cleaving caspases-3/8/9. Additionally, the protective effects of polysaccharide against hypoxia-induced apoptosis may be attributable to inactivate the ERK1/2 and PI3K/AKT signaling pathways (Wang et al, 2018). The polysaccharide of A. chinensis can be potentially used in the treatment of heart disease.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The results showed that with the delay in harvesting; there is an increase in pH and a decrease in Vitamin C in all cultivators. With the delay in harvesting the TPC (Total phenolic content) were decreased, while TFC (Total lavonoid content) increased in all tested cultivars (Pal et al, 2015;Wang et al, 2018). The highest concentration of the phenolic content and the lavonoid content were found in cultivator 'Allison' in the month of October and December.…”
Section: Discussionmentioning
confidence: 91%